PS-028 Monitoring the appropriate use of antipsychotics in adolescents in the health district of Cosenza (Italy). (24th February 2014) - Garreffa, M; Carbone, C; Vulnera, M; Piro, B
Abstract : Background: Recently there has been an increased use of antipsychotic drugs (APs), particularly atypicals, in the treatment of psychotic and behavioural disorders in adolescents. They may cause cardiometabolic effects, which may be predictive of obesity, metabolic syndrome, cardiovascular disease and cancer. Purpose: To evaluate the off-label use of all APs (N05A) in adolescents in the health district of Cosenza (Italy). Materials and methods: We used Excel and Access to analyse AP prescriptions in 2012 in the health district of Cosenza (780, 000 inhabitants) relating to patients aged 15–22. We looked at the characteristics of these drugs to check whether they were being used off-label in the study population. Results: We recorded 1681 prescriptions for 182 patients: 128 males, 54 females. In 25 patients off-label use was observed: the APs were employed in a range of ages for which safety data are not available. 2 patients aged under 16 were treated with clotiapine in co-treatment with other APs (risperidone, haloperidol); another one with clozapine in co-treatment with lithium. Despite the use of lithium only being allowed for a short time in the age range 12–18, we noticed protracted treatment of at least 1 year for a patient aged 16. Olanzapine, which is contraindicated in children and adolescents, was prescribed in 3 patients (15–16 years). Risperidone cannot be used for more than 6 months in paediatric and adolescent patients, but it was used in 14 patients aged between 15 and 17 years throughout the period under review. Conclusions: The analysis highlights the importance of comparing the prescription data with those in the treatment plan, to investigate the appropriateness. The safety data of antipsychotics in children and adolescents are limited, hence the importance of close monitoring of prescriptions and dissemination of briefings to specialists and general practitioners. No conflict of interest.